Comparative scientometric study of four pharmacy departments. - Goh, Bertrand Szer Lin. (2008)
This is a comparative scientometric study of four pharmacy departments from Singapore, Sydney, Nottingham and Buffalo State, New York. It aims to compare the publication outputs and extent of collaboration amongst researchers within each of these centers over twelve years from 1994 to 2005.